The Effect of Innovation and Digital Capital Adoption on MSME Performance Mediated by Competitive Advantage - Ramadhan, Mochammad Havid Rizqi; Kautsar, Achmad; Dewi, Renny Sari; Fazlurrahman, Hujjatullah (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Amid the accelerated advancement of digital technologies and the intensification of market rivalry, continuous enhancement of business performance among MSMEs has become imperative through innovation and digital transformation initiatives. Nevertheless, empirical investigations examining the contribution of digital capital adoption and innovation to MSME performance, particularly when competitive advantage functions as an intervening mechanism, remain relatively scarce, especially within regional MSME settings. This study is conducted to investigate the influence of innovation and digital capital adoption on MSME performance, with competitive advantage positioned as a mediating construct. A quantitative research design is employed, utilizing survey responses obtained from 90 MSME proprietors in Probolinggo Regency. The data that were gathered are processed and evaluated through PLS-SEM to assess both direct and indirect causal pathways among the examined variables. The results reveal that innovation is found to exert a significant positive effect on competitive advantage, which in turn is shown to significantly enhance MSME performance. On the other hand, there is no evidence that innovation directly affects the performance of MSMEs. However, adopting digital capital has been shown to have a big and positive effect on performance results. Moreover, the linkage between innovation and MSME performance is fully mediated by competitive advantage. These results suggest that innovation enhances MSME performance only when it is transformed into competitive advantage, whereas digital capital adoption directly contributes to performance improvement. Therefore, for MSME practitioners, strengthening innovation strategies oriented toward competitive differentiation and expanding the effective use of digital capital are essential to improve business performance.